Effect of crystalline transformation on supercritical CO2 foaming and cell morphology of isotactic polybutene-1 - Weijie Li; Zheng Gong; Kaiwen Wu; Ling Zhao; Dongdong Hu (Journal of CO2 Utilization, 2023)
As a polycrystalline polymer, isotactic polybutene-1 (iPB-1) will form different crystalline structures when it crystallizes under different conditions. In this work, we found a simple method to manipulate the cell structure of iPB-1 foams by controlling the annealing time of crystalline form II at room temperature and employing supercritical CO2 foaming. As the content of crystalline form II increases, the storage modulus (G′) and complex viscosity (|η * |) increase, and the solubility of CO2 in iPB-1 increases. Crystalline form II has a wider foaming temperature window compared to crystalline form I and exhibits a more uniform cell structure at temperatures between 95 °C and 125 °C. The average cell diameters of crystalline form II and I are 33.9 µm and 11.2 µm at 115 °C and 15 MPa CO2, respectively. A small amount of crystalline form I acts as a heterogeneous nucleation agent during the foaming process, resulting in the formation of a “petal-like” cell structure. During the foaming saturation process, the melted portion of iPB-1 with unstable crystalline form II transforms into crystalline form I′ under high-pressure CO2, while the unmelted portion transforms into crystalline form I. As the pressure increases, the cell structure of iPB-1 undergoes a transition from “petal-like” to bimodal cell structure, ultimately achieving a more uniform structure. Moreover, increasing foaming pressure can also change the cell structure of the foamed material from closed-cell to open-cell. The occurrence of bimodal melting peaks in the foamed samples is beneficial for the adhesion of beads during the molding process.